Macrophages and cadherins in fibrosis and systemic sclerosis. Issue 6 (November 2019) - To, Sarah; Agarwal, Sandeep K.
Abstract : Purpose of review: Macrophages are key players in systemic sclerosis (SSc) and fibrosis. The mechanism by which macrophages regulate fibrogenesis is unclear and understanding the origin and function of macrophages is critical to developing effective therapeutics. Novel targets on macrophages are under investigation and recently, cadherins have emerged as a potential therapeutic target on macrophages. The current review will discuss the importance of macrophages in SSc and fibrosis and summarize recent studies on the role of cadherin-11 (Cdh11) on macrophages and fibrosis. Recent findings: Genome-wide expression studies demonstrate the importance of macrophages in SSc and fibrosis. Although M2 macrophages are associated with fibrosis, the presence of a mixed M1/M2 phenotype in fibrosis has recently been reported. Several studies aiming to identify macrophage subsets involved in fibrogenesis suggest that monocyte-derived alveolar macrophages are key players in the development of murine lung fibrosis. Recent functional studies show that Cdh11 regulates macrophages, fibroblast invasion, and adhesion of macrophages to myofibroblasts. Summary: Macrophages play an important role in SSc and fibrosis. New insights into the mechanisms by which macrophages regulate fibrogenesis have been discovered on the basis of Cdh11 studies and suggest that targeting Cdh11 may be an effective target to treat fibrosis.